Adherence, perceptions and knowledge of an HIV PMTCT programme: A mother-baby pair study - Sthembiso Mabuka; Mygirl P. Lowane; Tintswalo V. Nesengani; Thembi V. Simbeni (Southern African Journal of HIV Medicine)
Background: Prevention of mother-to-child transmission (PMTCT) programmes are designed to prevent HIV transmission to infants and children. Despite efforts to achieve this goal, several factors continue to pose challenges.